(untitled) (International Journal of Engineering and Computer Science, 2016)
— Cryptography is a technique used to avoid unauthorized access of data. It has two main components; a) Encryption algorithm, and b) Key. Sometime, multiple keys can also be used for encryption. A number of cryptographic algorithms are available in market such as DES, AES, TDES and RSA. The strength of these encryption algorithms depends upon their key strength. Strong encryption algorithms and optimized key management techniques always help in achieving confidentiality, authentication and integrity of data and reduce the overheads of the system. The long key length takes more computing time to crack the code and it becomes difficult for the hacker to detect the cryptographic model. In this paper we suggest an innovation in the age-old conventional cryptographic technique of HILL-CIPHER using the concept of self repetitive matrix. A numerical method has been stated, mathematically proved and later implemented in generating a random matrix of given periodicity. The method of self-repetitive matrix has then been used to simulate a communication channel with proper decompression techniques to facilitate bit saving.